The Influence of Lifestyle, Financial Literacy, Love of Money, and Fintech Payment on Financial Management Behavior Among Accounting Students - Agnas, Felixia Renita; Akbar, Khairil; Kusumah, Angga (Kunuz: Journal of Islamic Banking and Finance, 2024)
This study investigates the determinants of financial management behavior (FMB) among Accounting students at a Polytechnic institution, focusing on lifestyle, financial literacy, love of money, and fintech payment as independent variables. Utilizing multiple linear regression analysis, the research explores the relationships between these variables and students' financial management practices. The findings indicate that financial literacy and fintech payment significantly influence FMB, with financial literacy showing a substantial positive effect (β = 0.387). Conversely, lifestyle and love of money were found to exert no statistically significant impact on financial management behavior. When analyzed collectively, the four independent variables demonstrated a significant simultaneous effect on FMB, as confirmed by the F-test. The study underscores the pivotal role of financial literacy and fintech adoption in shaping sound financial management among students in the digital era. The results suggest that educational institutions should prioritize integrated financial education programs to enhance students' financial competencies. Future research could expand the scope by incorporating additional variables, such as the influence of social media or students' spending patterns in the digital age. This research contributes valuable insights into the factors influencing financial management behavior and the growing relevance of digital financial tools in personal finance management.